PROPOSED STRATEGY FOR AURORA COMMERCE RETAIL TO SUSTAIN AND GROW ON THE ONLINE MARKETPLACE PLATFORM - Edmund Ophie; Harimukti Wandebori (JPIM (Jurnal Penelitian Ilmu Manajemen), 2024)
Online commerce is an activity of online buying and selling physical goods. Report by Momentum Works showed that the gross merchandise value (GMV) from major online marketplace platforms in Indonesia had reached $40 billion in 2020, which is 20% of total retail in the country. As of 2020, the two biggest platforms of online marketplace platforms in Indonesia are Tokopedia and Shopee, with both possess over 70% of the online commerce market share. Aurora Commerce Retail (ACR) is one amongst many stores that sells products on the online marketplace platforms. It specialized in retailing two main product categories of health supplements and kitchen electronics. Online retail business like what ACR does, is a very fragmented industry that consist of vast number of stores from small to medium size and generally with no single store or seller dominates the market. The online retail business has its own challenges from competing against other stores that sell similar or identical products tp an ever increasing platform cost. This study aims to develop corporate and business strategy for ACR in accordance to its current condition. The research collected the necessary data to conducts analysis on ACR's target consumers, external and internal environments. From the analysis, a SWOT matrix is developed and a suitable corporate and business strategy for ACR are constructed. Based on the research, ACR current condition is dominated by its strength and threat, putting it in the diversification quadrant. Therefore, the best directional strategy for ACR is to pursue diversification. To pursue a diversification strategy, ACR with its background in software engineering could expand into a software development company that specialize in building ecommerce operation supporting tools and software. Meanwhile, to maintain its current retail business, the proposed business strategy for ACR’s health supplements and kitchen electronics retailing business is to be narrow-target with cost-leadership that emphasizes ACR to focus on few select brands with competitive prices